Fiscal Policy for Economic Recovery and Development: An Empirical Investigation of Fiscal Policy Shocks in the Sri Lankan Economy - Fernando, T.D.N. (Department of Economics, University of Colombo, 2025)
This is an empirical investigation of fiscal policy transmission mechanisms in the Sri Lankan economy using a Real Business Cycle Dynamic Stochastic General Equilibrium (RBC-DSGE) model, motivated by Sri Lanka's severe economic crisis since 2022, including fiscal imbalances, rising debt, and macroeconomic instability. The RBC-DSGE model incorporates households, firms, and government fiscal policy through consumption expenditure, capital, and labor income taxation. Key findings from impulse response analysis reveal that Total Factor Productivity shocks have the strongest positive impact (1% increase generates 3% output growth), while government consumption shocks yield modest positive effects (fiscal multiplier: 1.587) but crowding-out of private investment. Capital income tax increases produce contractionary effects (multiplier: -0.16) through reduced investment, while labor income tax increases generate stronger contractionary effects (multiplier: -1.0545). Policy implications support productivity-enhancing measures, strategic government spending complementing the private sector, and careful tax policy design with minimizing distortions. This research contributes methodologically by applying RBC-DSGE techniques to Sri Lankan fiscal policy, providing empirical multiplier insights and evidence-based guidance for economic recovery.
Keywords: RBC-DSGE Model; Fiscal Policy; Sri Lankan Economy; Fiscal Multipliers; Tax Policy